NEONATAL PAIN MANAGEMENT PRACTICES AMONG NURSES WORKING IN NEWBORN UNITS IN NYANZA AND WESTERN KENYA - Teresa Kerubo Okiri; Mary Kipmerewo; Beatrice Mukabana (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2023)
Background: Newborn babies in the Neonatal Intensive Care Units (NICU) and Newborn Units (NBUs) undergo several procedures that cause a significant amount of pain. Nurses play an essential role in the implementation of pain assessment and management measures in neonates. However, while it remains widely known that nurses play an important role in neonatal pain management, nurses’ practices on the management of pain in neonates admitted in Newborn care units have not been widely published within the nursing science. Objectives: To evaluate neonatal pain management practices among nurses working in newborn units in Nyanza and Western Kenya. Methods: A descriptive cross-sectional study using qualitative and quantitative approaches was used targeting 89 nurses. The collection of data was done through semi-structured, self-administered questionnaires with both closed and open –ended questions. Qualitative data was collected through in-depth interviews. Data obtained was analyzed using the statistical package for social science (SPSS) version 22.0 software. The study assumed a confidence level of 95% and a (p) value equal to or less than 0.05 was considered significant. Qualitative data was analyzed through logic checks to understand the emerging themes. Descriptive statistical analysis was done using frequencies, percentage and means. Results: The study established that a small percentage of the nurses practiced pain management in neonates through use of non-pharmacologic (34.8%) and pharmacologic (28.1%) strategies. The commonly used non-pharmacologic strategies include changing of nappies (71.9%) and repositioning (68.5). Pain assessment was however seldom done. Conclusion: Following the results, the study concluded that nurses practice pain management in neonates by implementing non-pharmacological and pharmacological strategies. The commonly used pain management strategy in neonates is utilization of non-pharmacological strategies such as change of nappies repositioning and kangaroo mother care. However, gaps exist in knowledge and competency on neonatal pain management aspects and practice. The study therefore recommended enhancement of awareness on aspects of neonatal pain among nurses to facilitate improved pain management practices in neonates. Further strengthening of nurses’ knowledge and skills on pain management in neonates through attending scheduled short courses, workshops and on job training is recommended.